Position of the American Dietetic Association, dietitians of Canada, and the American College of Sports Medicine: Nutrition and athletic performance (Journal of the American Dietetic Association, 2009)
This American Dietetic Association (ADA) position paper uses ADA`s Evidence Analysis Process and information from ADA`s Evidence Analysis Library. Similar information is also available from Dietitians of Canada`s Practice-based Evidence in Nutrition. The use of an evidence-based approach provides important added benefits to earlier review methods. The major advantage of the approach is the more rigorous standardization of review criteria, which minimizes the likelihood of reviewer bias and increases the ease with which disparate articles may be compared. For a detailed description of the methods used in the evidence analysis process, access ADA`s Evidence Analysis Process at http://adaeal.com/eaprocess/. Conclusion Statements are assigned a grade by an expert work group based on the systematic analysis and evaluation of the supporting research evidence. Grade I Good, Grade II Fair, Grade III Limited, Grade IV Expert Opinion Only, and Grade V Grade Is Not Assignable (because there is no evidence to support or refute the conclusion). Evidence-based information for this and other topics can be found at www.adaevidencelibrary.com and www.dieteticsatwork.com/pen and subscriptions for non-ADA members are available for purchase at https:// www.adaevidencelibrary.com/store.cfm. Subscriptions for Dietitians of Canada and non-Dietitians of Canada members are available for Practicebased Evidence in Nutrition at http://www.dieteticsatwork.com/pen_order.asp.